Multicultural Classroom Issues in the Nepalese Context - Subedi, Dhanapati (Journal of Education and Research, 2010)
Multicultural issue in the present context is a global issue of socialization. It has not yet been materialized into the education system in Nepal. The education system of a country should prepare students to function in today’s diverse society. There are issues emerging in the effectiveness of the multicultural education and the concerns how to better shape the multicultural classroom in Nepal. This paper focuses on issues such as curriculum design, classroom management, and role of teachers and students in the multicultural classroom context. It also discusses the context, and recommends measures that can bring the multicultural education into the right track. DOI: http://dx.doi.org/10.3126/jer.v2i0.7618 Journal of Education and Research Vol. 2, 2010 p.17-25